TENAGA KERJA OUTSOURCING DALAM TINJAUAN HUKUM ISLAM DAN UU NO 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - Aye Sudarto (Nizham Jurnal Studi Keislaman, 2019)
In the implementation of national development, labor has a very important role and position as an actor and development goal. The workforce itself is the driving force of the company, work partners, company assets which are investments for a company in order to increase productivity. Labor is also the most important asset in an effort to increase the volume of development. In accordance with the role and position of the workforce, development in the field of labor is needed to improve the quality of the workforce and its participation in development and to increase the protection of workers in accordance with the dignity and dignity of humans. In this paper what will become folus is comparing the outsourcing workforce in dealing with Islamic law and UU 13 2003 concerning employment. So that it can see and present relevance to the lives of people today. There are similarities and differences between Islamic Law and UU No. 13 2003 concerning Manpower. both have the same goal, namely to create a sense of justice for all levels of society, especially for workers and employers, and do not allow for arbitrariness of workers / labor. While the difference lies in work relations, welfare, wages and government functions